2000
DOI: 10.1520/gtj11055j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Properties of Granulated Rubber/Sand Mixtures

Abstract: Processed waste tires mixed with soils are applicable in lightweight fills for slopes, retaining walls, and embankments that may be subjected to seismic loads. Rubber's high damping capacity permits consideration of granulated rubber/soil mixtures as part of a damping system to reduce vibration. The dynamic properties of granulated rubber/soil mixtures are essential for the design of such systems. This research investigates the shear modulus and damping ratio of granulated rubber/sand mixtures using a torsiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(37 citation statements)
references
References 6 publications
3
34
0
Order By: Relevance
“…A similar behavior, this time regarding the stiffness and damping ratio, was observed by Pamukcu and Akbulut [15]. Feng and Sutter [11], and Anastasiadis et al [33] reported that when the waste tire content was increased in a given waste tire and sand mixture, this resulted in a decrease of stiffness and an increase of damping ratio of the mixture. Anastasiadis et al [33] also showed that these changes in the properties of the mixture occurred in a close-to-linear fashion when the waste tire ratio allowed to be changed in the range of medium to high strain level.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…A similar behavior, this time regarding the stiffness and damping ratio, was observed by Pamukcu and Akbulut [15]. Feng and Sutter [11], and Anastasiadis et al [33] reported that when the waste tire content was increased in a given waste tire and sand mixture, this resulted in a decrease of stiffness and an increase of damping ratio of the mixture. Anastasiadis et al [33] also showed that these changes in the properties of the mixture occurred in a close-to-linear fashion when the waste tire ratio allowed to be changed in the range of medium to high strain level.…”
Section: Introductionsupporting
confidence: 74%
“…Conversely, mixtures with higher waste material ratios were observed to possess a relatively elastic response. As Feng and Sutter [11] also reported in their investigations, damping response in a given waste tire -sand mixture may be resulting from (i) the friction between each particle or (ii) the deformation of each particle. Particles of sand are known to be stiff, which explains why they dissipate small amounts of energy during deformation.…”
Section: Analysis Of Test Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…On the other hand, the reuse of shredded tires has great potential in geotechnical engineering programs, where rubber-soil mixtures (RSMs) are often used in lightweight backfill, highway embankments, soil reinforcement, and retaining walls [4]. Such large-scale geotechnical applications of recycled rubber can consume tremendous numbers of waste tires.…”
Section: Need For Seismic Hazard Mitigation In Less-developed Regionsmentioning
confidence: 99%